2016
DOI: 10.1038/srep30805
|View full text |Cite
|
Sign up to set email alerts
|

Essential role of the nuclear isoform of RBFOX1, a candidate gene for autism spectrum disorders, in the brain development

Abstract: Gene abnormalities in RBFOX1, encoding an mRNA-splicing factor, have been shown to cause autism spectrum disorder and other neurodevelopmental disorders. Since pathophysiological significance of the dominant nuclear isoform in neurons, RBFOX1-isoform1 (iso1), remains to be elucidated, we performed comprehensive analyses of Rbfox1-iso1 during mouse corticogenesis. Knockdown of Rbfox1-iso1 by in utero electroporation caused abnormal neuronal positioning during corticogenesis, which was attributed to impaired mig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
57
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 77 publications
(57 citation statements)
references
References 61 publications
0
57
0
Order By: Relevance
“…The regulation of these long neuronal genes is further complicated by intricate splicing dynamics 50,51 , which require highly dynamic and adaptive responses based on neuronal activation state. It is therefore not surprising that for many of these long genes, including for Nrxn3, Rbfox1 and Nlgn1, genetic variants are often associated with or directly result in neuronal diseases [60][61][62] . Thus, understanding how genome folding relates with the response to environmental challenges is increasingly important to further our understanding of the mechanisms of neurological disease.…”
Section: Discussionmentioning
confidence: 99%
“…The regulation of these long neuronal genes is further complicated by intricate splicing dynamics 50,51 , which require highly dynamic and adaptive responses based on neuronal activation state. It is therefore not surprising that for many of these long genes, including for Nrxn3, Rbfox1 and Nlgn1, genetic variants are often associated with or directly result in neuronal diseases [60][61][62] . Thus, understanding how genome folding relates with the response to environmental challenges is increasingly important to further our understanding of the mechanisms of neurological disease.…”
Section: Discussionmentioning
confidence: 99%
“…(62–65) Animal models have shown that RBFOX1 is involved in mouse corticogenesis and aggressive behaviours. (62,64,66,67) POLR3C is included in a well-known small CNV located at 1q21.1, which contributes to a broad spectrum of phenotypes in addition to ADHD, including morphological features and autism spectrum disorders (ASD). (68,69) Genes listed in Table 1 may be viewed as having, individually, the highest credibility as ADHD candidate genes.…”
Section: Discussionmentioning
confidence: 99%
“…However, whether Rbfox2 is expressed in mouse satellite cells, and/or functions during skeletal muscle development, growth, and/or regeneration has not been studied. The closest murine Rbfox1l homolog, Rbfox1, is primarily studied as a regulator of neuronal splicing (Gehman et al, 2011; Hamada et al, 2016; O’Brien et al, 2012; Weyn-Vanhentenryck et al, 2015), but is also expressed in heart and skeletal muscle (Kalsotra et al, 2008; Kiehl et al, 2001; Underwood et al, 2005). Surprisingly, conditional and partial Rbfox1 depletion in satellite cells does not affect muscle regeneration, with the caveat that only ~70% knockdown was achieved (Pedrotti et al, 2015).…”
Section: Discussionmentioning
confidence: 99%